KOMUNIKASI REMAJA PENDERITA SELF HARM MELALUI PENDEKATAN PENETRASI SOSIAL DI KOTA PEKANBARU - Deviani Fauzi; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The phenomenon of self-injury or self-harm is an “iceberg” phenomenon, because basiclly there are more people with self-harm than there are concrete data. May self-harm suffers come from among adolescents, because during adolescence there are physical and psychological changes. This is becauze, when adolescence is confused in overcoming a problem, the teeneger may do undesirable things such as self-harm, therefore effective interpersonal relationships are needed. The purposes of this study was to determine the process of social penetration of adolescents wit self-harm in establishing communication in Pekanbaru City and to determine the communication process formed in adolescents with self-harm to their families and friends in Pekanbaru City.           This study uses a qualitative research method with a phenomenological approach. Where this approach is carried out with the experience of informants used as a source of data which usually comes from quite long interviews with individuals who have in-depth experience and knowledge regarding the phenomena being studied. To determine the informant, the writer uses the snowball technique by determining the key informant that will lead the author to find the next informant. There were 2 informants in the study and this research was conducted in Pekanbaru City. This research was conducted from January to August 2020.          Based on the findings of the results in the field, the social penetration process that exists in self-harm adolescents shows that self-harm adolescents tend to cover up their activities of doing self-harm to their family and friends. However, self-harm adolescents tend to tell friends what motivates or causes them to do self-harm. The self-harm adolescents that the authors found turned out to be doing self-harm due to ineffective relationships found in their families, which led to these teens engaging in self-harm activities. Key words: self-harm; teenager; communication.